2018
DOI: 10.1099/jgv.0.001077
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and genome characteristics of canine astrovirus in southwest China

Abstract: The aim of this study was to investigate canine astrovirus (CaAstV) infection in southwest China. We collected 107 faecal samples from domestic dogs with obvious diarrhoea. Forty-two diarrhoeic samples (39.3 %) were positive for CaAstV by RT-PCR, and 41/42 samples showed co-infection with canine coronavirus (CCoV), canine parvovirus-2 (CPV-2) and canine distemper virus (CDV). Phylogenetic analysis based on 26 CaAstV partial ORF1a and ORF1b sequences revealed that most CaAstV strains showed unique evolutionary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 30 publications
4
24
2
Order By: Relevance
“…These recombination patterns were supported by RDP, GENECONV, MaxChi, Chimaera, SiScan, 3Seq, LARD, Phylpro and Bootscan programs as shown in Table 2. The potential recombination event 2 reported in this study supports the previous suggestion that the ORF1b/ORF2 junction region is prone to the recombination region in AstVs [49,50]. The co-existence of different PoAstVs within swine farms is absolutely possible due to the high prevalence of PoAstV in swine farms [3,12], and this may promote co-infections of one animal with more than one AstV strain at the same time as observed in this study.…”
Section: Recombination Analysissupporting
confidence: 88%
See 1 more Smart Citation
“…These recombination patterns were supported by RDP, GENECONV, MaxChi, Chimaera, SiScan, 3Seq, LARD, Phylpro and Bootscan programs as shown in Table 2. The potential recombination event 2 reported in this study supports the previous suggestion that the ORF1b/ORF2 junction region is prone to the recombination region in AstVs [49,50]. The co-existence of different PoAstVs within swine farms is absolutely possible due to the high prevalence of PoAstV in swine farms [3,12], and this may promote co-infections of one animal with more than one AstV strain at the same time as observed in this study.…”
Section: Recombination Analysissupporting
confidence: 88%
“…These novel viruses may potentially cross species barriers at some point. Many prior studies have reported evidence for recombination amongst astrovirus types in human, pigs, marine mammals, turkey, small ruminants and dogs [49,[51][52][53][54]. (Table S5).…”
Section: Recombination Analysismentioning
confidence: 99%
“…These recombination patterns were supported by RDP, GENECONV, MaxChi, Chimaera, SiScan, 3Seq, LARD, Phylpro, and Bootscan programs, as shown in Table 2. Potential recombination event 2 reported in this study supports the previous suggestion that the ORF1b/ORF2 junction region is prone to the recombination region in AstVs [51,52]. The co-occurrence of different strains within swine farms is certainly feasible due to the high incidence of PoAstV in swine farms [2,43], and this may promote co-infections of individual pigs with multiple strains at the same time, as observed in this study.…”
Section: Recombination Analysissupporting
confidence: 88%
“…These novel viruses may potentially cross species barriers at some point. Previous studies have found evidence for recombination amongst astrovirus serotypes in humans, pigs, marine mammals, turkeys, small ruminants, and dogs [51,[53][54][55][56].…”
Section: Recombination Analysismentioning
confidence: 98%
“…Each ORF encodes a different protein, with different degrees of sequence conservation. Compared with other genes, the Cap gene is most highly conserved [ 8 ], indicating that the design of specific primers in this gene is appropriate. CaAstV was first reported in 1980 in the USA [ 9 ].…”
Section: Introductionmentioning
confidence: 99%